Identifying Barriers to Effective Patient-Provider Communication About Food Insecurity Screenings in Outpatient Clinical Settings in Central Florida: A Mixed-Methods Study. Issue 2 (4th March 2022) - Bernhardt, Christina; Hou, Su-I; King, Christian; Miller, Ann
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objective: Screening for food insecurity in health care settings is inconsistently performed among health care providers. This study examined how patient-provider interactions influenced patient comfort discussing food insecurity, an important social determinant of health. Design: We conducted a convergent mixed-methods study and surveyed patients on their experiences with patient-centered care when communicating and interacting with their providers, and their comfort level being screened for food insecurity. Telephone interviews were also conducted to better understand the concepts in the survey. Setting: Various clinical organizations in Central Florida, as well as food pantries affiliated with Second Harvest Food Bank. Participants: Forty-six patients in Central Florida completed the survey, 12 of whom completed qualitative portions of the study (7 completing the qualitative survey questions and 5 completing a telephone interview). Main Outcome Measure: Patient comfort discussing food insecurity with their health care providers. Results: Quantitative findings show that patient involvement in care planning and cultural sensitivity of health care providers were 2 important factors associated with patient comfort being screened for food insecurity. Qualitative findings suggest that providers' effective communication and empathy are other factors that can influence patient comfort. Conclusion: To effectively address food insecurity of vulnerable patients and communities, it is important that providers conduct screenings within their practice. This study points to specific actions that providers may employ to increase patient comfort discussing this topic. Efficiently identifying food-insecure patients and connecting them to appropriate community resources would improve patient health and aid in efforts to eliminate health disparities.